Kinetic model of TBP auto-regulation exhibits bistability - Gokhale, Sucheta A.; Roshan, Reema; Khetan, Vivek; Pillai, Beena; Gadgil, Chetan J. (Biology Direct, 2010)
Background: TATA Binding Protein (TBP) is required for transcription initiation by all three eukaryotic RNA polymerases. It participates in transcriptional initiation at the majority of eukaryotic gene promoters, either by direct association to the TATA box upstream of the transcription start site or by indirectly localizing to the promoter through other proteins. TBP exists in solution in a dimeric form but binds to DNA as a monomer. Here, we present the first mathematical model for auto-catalytic TBP expression and use it to study the role of dimerization in maintaining the steady state TBP level. Results: We show that the autogenous regulation of TBP results in a system that is capable of exhibiting three steady states: an unstable low TBP state, one stable state corresponding to a physiological TBP concentration, and another stable steady state corresponding to unviable cells where no TBP is expressed. Our model predicts that a basal level of TBP is required to establish the transcription of the TBP gene, and hence for cell viability. It also predicts that, for the condition corresponding to a typical mammalian cell, the high-TBP state and cell viability is sensitive to variation in DNA binding strength. We use the model to explore the effect of the dimer in buffering the response to changes in TBP levels, and show that for some physiological conditions the dimer is not important in buffering against perturbations. Conclusions: Results on the necessity of a minimum basal TBP level support the in vivo observations that TBP is maternally inherited, providing the small amount of TBP required to establish its ubiquitous expression. The model shows that the system is sensitive to variations in parameters indicating that it is vulnerable to mutations in TBP. A reduction in TBP-DNA binding constant can lead the system to a regime where the unviable state is the only steady state. Contrary to the current hypotheses, we show that under some physiological conditions the dimer is not very important in restoring the system to steady state. This model demonstrates the use of mathematical modelling to investigate system behaviour and generate hypotheses governing the dynamics of such nonlinear biological systems.

Regulation of BACE1 by miR-29a/b in a cellular model of spinocerebellar ataxia 17 - Roshan, Reema; Ghosh, Tanay; Gadgil, Mugdha; Pillai, Beena (RNA Biology, 2012)
Polyglutamine diseases are a class of neurodegenerative disorders characterized by expansion of polyglutamine repeats, protein aggregation and neuronal cell death in specific regions of the brain. The expansion of a polyglutamine repeat in the TATA binding protein (TBP) causes a neurodegenerative disease, Spinocerebellar Ataxia 17 (SC A17). This disease is characterized by intranuclear protein aggregates and selective loss of cerebellar neurons, including Purkinje cells. MicroRNAs are small, endogenous, regulatory non-coding RNA molecules that bind to mRNAs with partial complementarity and interfere in their expression. Here, we used a cellular model of SC A17 where we expressed TBP with 16 (normal) or 59 (pathogenic) polyglutamines and found differential expression of several microRNAs. Specifically, we found two microRNAs, miR-29a/b, were downregulated. With miR-29a/b downregulation, we found an increased expression of targets of miR-29a/b-beta-site amyloid precursor protein cleaving enzyme 1 (BACE 1), p53 upregulated modulator of apoptosis (PUMA) and BAK, increased cytochrome c release and apoptosis. Restoration of miR-29a/b in the pathogenic polyglutamine background reduced the BACE 1 expression. While, antagomiRs against miR-29a/b resulted in an increase in BACE 1 levels and neuronal apoptosis. In spite of the elevation of BACE 1 in Alzhemiers disease, its role in neuronal cell death has not been established. Here, we show that increased BACE 1 expression is not sufficient to cause apoptosis. However restoring level of BACE 1 to normal in polyglutamine cells partially reduced neuronal apoptosis. We show a role for the miR-29a/b-BACE 1 regulatory interaction in SC A17, suggesting that this microRNA could be part of a common molecular mechanism leading to neuronal cell death in multiple neurodegenerative disorders. The identification of a common mechanism of microRNA mediated neurodegeneration not only improves our understanding of the process, but also provides promising and novel therapeutic targets.
Keywords: BACE1; miR-29a/b; neurodegeneration; SCA17; TBP

Detection and knockdown of MicroRNA-34a using thioacetamido nucleic acid - Soni, Kartik; Gupta, Shivani; Gokhale, Sachin S.; Dey, Rakesh; Gunjal, Anita D.; Kumar, Vaijayanti A.; Pillai, Beena (Nucleic Acid Therapeutics, 2013)
Thioacetamido nucleic acids (TANA) contain a backbone modification of dinucleotides consisting of a 5-atom amide linker N3'-COCH2-S-CH2 at thymidine or thymidine-cytidine dimer blocks. Here, the chemical synthesis of the TANA linked 5-methyl-cytidine-cytidine ((Me)cc) dimer block and its incorporation into the DNA sequence, complementary to human microRNA 34 (miR-34) is described. Further, for the first time, we demonstrate the biological applications of TANA modified oligonucleotides in detection and intracellular knockdown of a cancer related microRNA in comparison with DNA containing locked nucleic acid (LNA) and 2'-O-methyl modifications. The human microRNA miR-34 is a pro-apoptotic microRNA under the transcriptional control of protein 53 (p53). It gets expressed in response to DNA damage and regulates several cell cycle and apoptosis related targets. Here, we show that the TANA modified antisense oligonucleotide binds specifically to miR-34a, allowing its detection using primer extension. We also show that, using the TANA modified antisense oligonucleotide against miR-34a, intracellular levels of miR-34 can be reduced, and consequently, the expression of its target oncogene V-myc myelocytomatosis viral related oncogene, neuroblastoma derived (MYCN) is enhanced. Further, we assessed the toxicity and serum stability of the oligonucleotide to conclude that it is suitable for detection and modulation of the vital biomarker and tumor suppressor microRNA.

Non-coding RNA interact to regulate neuronal development and function - Iyengar, Bharat R.; Choudhary, Ashwani; Sarangdhar, Mayuresh A.; Venkatesh, K. V.; Gadgil, Chetan J.; Pillai, Beena (Frontiers in Cellular Neuroscience, 2014)
The human brain is one of the most complex biological systems, and the cognitive abilities have greatly expanded compared to invertebrates without much expansion in the number of protein coding genes. This suggests that gene regulation plays a very important role in the development and function of nervous system, by acting at multiple levels such as transcription and translation. In this article we discuss the regulatory roles of three classes of non-protein coding RNAs (ncRNAs)-microRNAs (miRNAs), piwi-interacting RNA (piRNAs) and long-non-coding RNA (lncRNA), in the process of neurogenesis and nervous function including control of synaptic plasticity and potential roles in neurodegenerative diseases. miRNAs are involved in diverse processes including neurogenesis where they channelize the cellular physiology toward neuronal differentiation. miRNAs can also indirectly influence neurogenesis by regulating the proliferation and self renewal of neural stem cells and are dysregulated in several neurodegenerative diseases. miRNAs are also known to regulate synaptic plasticity and are usually found to be co-expressed with their targets. The dynamics of gene regulation is thus dependent on the local architecture of the gene regulatory network (GRN) around the miRNA and its targets. piRNAs had been classically known to regulate transposons in the germ cells. However, piRNAs have been, recently, found to be expressed in the brain and possibly function by imparting epigenetic changes by DNA methylation. piRNAs are known to be maternally inherited and we assume that they may play a role in early development. We also explore the possible function of piRNAs in regulating the expansion of transposons in the brain. Brain is known to express several lncRNA but functional roles in brain development are attributed to a few lncRNA while functions of most of the them remain unknown. We review the roles of some known lncRNA and explore the other possible functions of lncRNAs including their interaction with miRNAs.
Keywords: gene expression regulation; lncRNA; miRNA; network-motifs; piRNA

Systematic comparison of the response properties of protein and RNA mediated gene regulatory motifs - Iyengar, Bharat Ravi; Pillai, Beena; Venkatesh, K. V.; Gadgil, Chetan J. (Molecular BioSystems, 2017)
We present a framework enabling the dissection of the effects of motif structure (feedback or feedforward), the nature of the controller (RNA or protein), and the regulation mode (transcriptional, post-transcriptional or translational) on the response to a step change in the input. We have used a common model framework for gene expression where both motif structures have an activating input and repressing regulator, with the same set of parameters, to enable a comparison of the responses. We studied the global sensitivity of the system properties, such as steady-state gain, overshoot, peak time, and peak duration, to parameters. We find that, in all motifs, overshoot correlated negatively whereas peak duration varied concavely with peak time. Differences in the other system properties were found to be mainly dependent on the nature of the controller rather than the motif structure. Protein mediated motifs showed a higher degree of adaptation i.e. a tendency to return to baseline levels; in particular, feedforward motifs exhibited perfect adaptation. RNA mediated motifs had a mild regulatory effect; they also exhibited a lower peaking tendency and mean overshoot. Protein mediated feedforward motifs showed higher overshoot and lower peak time compared to the corresponding feedback motifs.

Amino acid abundance and composition in cell culture medium affects trace metal tolerance and cholesterol synthesis - Rawat, Jyoti; Bhambri, Aksheev; Pandey, Ujjiti; Banerjee, Sanchita; Pillai, Beena; Gadgil, Mugdha (Biotechnology Progress, 2023)
Amino acid compositions of cell culture media are empirically designed to enhance cell growth and productivity and vary both across media formulations and over the course of culture due to imbalance in supply and consumption. The interconnected nature of the amino acid transporters and metabolism suggests that changes in amino acid composition can affect cell physiology. In this study, we explore the effect of a step change in amino acid composition from a DMEM: F12-based medium to a formulation varying in relative abundances of all amino acids, evaluated at two amino acid concentrations (lean LAA vs. rich HAA). Cell growth was inhibited in LAA but not HAA. In addition to the expected effects on expression of the cell cycle, amino acid response and mTOR pathway genes in LAA, we observed an unanticipated effect on zinc uptake and efflux genes. This was accompanied by a lower tolerance to zinc supplementation in LAA but not in the other formulations. Histidine was sufficient but not necessary to prevent such zinc toxicity. Additionally, an unanticipated downregulation of genes in the cholesterol synthesis pathway was observed in HAA, accompanied by an increase in cellular cholesterol content, which may depend on the relative abundances of glutamine and other amino acids. This study shows that changes in the amino acid composition without any evident effect on growth may have profound effects on metabolism. Such analyses can help rationalize the designing of medium and feed formulations for bioprocess applications beyond replenishment of consumed components.
Keywords: Amino acids; cell culture medium; CHO cells; Cholesterol; zinc